Situation Report: Poland, 7 April 1981 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Bydgoszcz Incident: Background, Chronology, and Negotiations Poland's Democratic Party Votes for Democracy The Democratic Youth Union Agricultural Circles to Assume the Role of Trade Unions Polish Debts: The Worst Possible Scenario Unlikely to Occur